ANALISIS KEMAMPUAN BERPIKIR KRITIS MATA PELAJARAN KIMIA PADA SISWAKELAS XI IPA SMAN 1 KEPAHIANG - Selly Yunita; Salastri Rohiat; Hermansyah Amir (ALOTROP, 2018)
[ANALYSIS OF THE CRITICAL THINKING ABILITY FROM CHEMICAL SUBJECTS IN STUDENTS OF CLASS XI IPA SMAN 1 KEPAHIANG] This research aims to know the critical thinking ability of students. Type of this research is descriptive research using quantitative methods. This research was carried out in SMA Negeri 1 Kepahiang on September 2 to 8 may in 2017. The population in this research is the entire class XI IPA are registered on the even-numbered school year 2016/2017 semester. As the samples are taken at class XI IPA 6 of 32 participants.  Data collection is done with the test in the form of reserved descriptions as much as 10 round the whole includes indicators of critical thinking from the taxonomy of Bloom that is level (C2) understand (C3), apply (C4), analyzing and evaluating (C5). Test results obtained from the analysis of results the percentage of students with the ability to answer a question of thinking very critically at 15,6%, quite critical at 53,2 %, and less critical at 31,2 %, with an average value of 61.81. From the average of the values obtained showed that students who have average value included in the category of being. Based on the analysis of the data collected can be inferred levels of critical thinking ability of the students in class XI IPA 6 SMA Negeri 1 Kepahiang at school 2016/2017 academic year can be grouped in a category group are of 53,2 %, middle , 15,6 %  at high group and 31,2 % at low groups. From the results, it can be concluded that overall students in grades at  XI IPA 6 SMA Negeri 1 Kepahiang even 2016/2017 academic year with the ability to enough think critically.